Using learning analytics to engage students: Improving teaching practices through informed interactions - Justina Naujokaitienė; Giedrė Tamoliūnė; Airina Volungevičienė; Josep M. Duart (Springer, 2020)
Abstract Student engagement is one of the most relevant topics within the academic and research community nowadays. Higher education curriculum, teaching and learning integrate new technology- supported learning solutions. New methods and tools enhance teacher and learner interactions and influence learner engagement positively. This research addresses the need to explore new ways of improving teaching practices to better engage students with the help of learning analytics. The paper investigates how university teachers use the data from learning analytics to observe learners and to engage them in online learning. Qualitative inquiry was chosen to approach the research problem, and semi-structured interviews with the teachers using (blended) online learning were conveyed to explore teacher practices in students' behaviour and engagement observations online, disclosing teachers' abilities to understand the challenging learner engagement process based on the data from learning analytics. The new evidence provided by this research highlights the successful practices in the use of learning analytics data to observe students' behaviour and engagement and to inform teachers on the presence needed in order to develop learner-centred activities and to make curriculum changes. The limitation of this study lies in the fact that the different online teaching experiences that research participants had might have restricted their understanding of the use of LA data for curriculum development and learners' engagement.